ANALYSIS OF IMPROVING ORGANIZATIONAL COMPETITIVENESS THROUGH IMPLEMENTATION OF SIMRS SECURITY SYSTEM IN HOSPITALS: LITERATURE REVIEW - Ranita Rizky Putri; Kosasih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This literature review aims to analyze the role of Hospital Management Information System (SIMRS) security in enhancing the organizational competitiveness of hospitals in Indonesia. SIMRS has become a crucial instrument in supporting efficiency, transparency, and the quality of healthcare services. However, the growing use of electronic medical records also presents serious challenges related to patient data security and privacy. This study reviews 10 national publications issued between 2017 and 2025, focusing on SIMRS security issues. The findings reveal that the main challenges lie in weak access control, insufficient encryption, limited audit logs, and the suboptimal implementation of basic security features such as auto logout. Moreover, patient privacy aspects such as consent mechanisms, role-based access, and the principle of data minimization are rarely applied. Managerial factors, including low awareness among healthcare staff and weak internal policies, further exacerbate security risks. Overall, the success of SIMRS implementation is determined not only by technological sophistication but also by regulatory compliance, managerial commitment, and ethical awareness among healthcare workers. Strengthening SIMRS security is considered a strategic investment to enhance patient trust, strengthen hospital reputation, and support organizational competitiveness in the digital era.